2001
DOI: 10.1093/emboj/20.10.2536
|View full text |Cite
|
Sign up to set email alerts
|

Dnmt3a binds deacetylases and is recruited by a sequence-specific repressor to silence transcription

Abstract: F.Fuks and W.A.Burgers contributed equally to this workThe Dnmt3a DNA methyltransferase is essential for mammalian development and is responsible for the generation of genomic methylation patterns, which lead to transcriptional silencing. Here, we show that Dnmt3a associates with RP58, a DNA-binding transcriptional repressor protein found at transcriptionally silent heterochromatin. Dnmt3a acts as a corepressor for RP58 in a manner that does not require its de novo methyltransferase activity. Like other charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
355
1
4

Year Published

2002
2002
2011
2011

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 502 publications
(376 citation statements)
references
References 51 publications
16
355
1
4
Order By: Relevance
“…All of them have been shown to interact directly with the mSin3A-HDACs complex (Robertson et al, 2000;Rountree et al, 2000;Fuks et al, 2001;Datta et al, 2003). In this study, we have revealed that Dnmt3a and Dnmt3b are novel partners of the Ets family transcription factor PU.1.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…All of them have been shown to interact directly with the mSin3A-HDACs complex (Robertson et al, 2000;Rountree et al, 2000;Fuks et al, 2001;Datta et al, 2003). In this study, we have revealed that Dnmt3a and Dnmt3b are novel partners of the Ets family transcription factor PU.1.…”
Section: Discussionmentioning
confidence: 76%
“…In vitro translated 35 S-labeled luciferase, CBP1890, MeCP2, Dnmt3a and Dnmt3b were incubated with the 50% slurry of 20 ml of immobilized GST protein and GST-PU.1 fusion protein, and bound proteins were subjected to Nu-PAGE followed by autoradiography. Epigenetic transcriptional repression of PU.1-mediated reporter activity by Dnmt3s Several studies have shown that Dnmt3a and Dnmt3b are associated with HDAC1 and HDAC2 in vivo and in vitro (Robertson et al, 2000;Bachman et al, 2001;Fuks et al, 2001). Histone deacetylase removes the acetyl groups from the amino-terminal of the histone tails, which triggers the assembly of a tightly packed chromatin inaccessible to the transcriptional machinery (Jenuwein and Allis, 2001).…”
Section: Resultsmentioning
confidence: 99%
“…For example, activation of RAS [MacLeod et al, 1995], down regulation of Rb [Slack et al, 1999], or upregulation of the Wnt signaling pathway [Campbell and Szyf, 2003] leads to increased expression of DNMT1. Certain oncogenes could target DNMT to tumor suppressor genes and thus bring about regional hypermethylation [Fuks et al, 2001;Di Croce et al, 2002;Brenner et al, 2005;Vire et al, 2006]. An interesting possibility is that aberrant DNA methylation of cancer related genes could also come about through activation of signaling pathway by different environmental exposures, which might also include social exposures.…”
Section: Epigenetic Plasticity and Late Onset Pathologymentioning
confidence: 99%
“…For example DNA methyltransferases are known to independently recruit histone deacetylases, leading to histone deacetylation and transcriptional repression (28,29). In addition, MBDs can independently recruit HDACs to the site of DNA methylation (3,30).…”
Section: Introductionmentioning
confidence: 99%